Analysis of the Challenges and Technical Solutions for Revitalization of Traditional Buildings in Hot and Humid Climate (Case Study: Anthropology Museum of Local Residents in Kish Island) - Soroush Nikeghbali; Ali Damavandi (Salehan Institute of Higher Education, 2018)
In every nation ancient buildings are rich sources for inspiration from local traditional architecture. Manu of such buildings still have potentials for conservation and renovation. This article reviews the issue of revitalization of old traditional buildings in south part of Iran with hot and humid climate. The key technical challenges of revitalization and renovation of such buildings were explored via literature review. Then, the technical solution for such challenges were identified via cases study analysis. In order to reach comprehensive and practical solutions, tree key field of built environment studies which are architecture, structure and infrastructure design were explored together. The case study for this research was the project of revitalization of a traditional building into “Anthropology Museum of Local Residents” in Kish Island. The analysis and case study showed that most of the technical challenges for revitalization of such buildings are resolvable via simple solutions. Based on this, economic and socio-cultural supports of local authorities and planning departments are necessary in order to make such revitalization projects more feasible.